Yearbook of the international free trade union movement / preface by J.H. Oldenbroek - Oldenbroek, Jacobus H. (Jacobus Hendrik)
Anual | En portada: Published under the auspices of The International Confederation of Free Trade UnionsDescripción basada en: 1957/1958